2021
DOI: 10.1002/adhm.202100078
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology: Breaking the Current Treatment Limits of Lung Cancer

Abstract: Lung cancer is one of the most rapidly growing malignancies in terms of morbidity and mortality. Although traditional treatments have been used for more than 50 years, it is still far from solving the problems of postoperative risks and systemic toxicity. Emerging targeting and immunotherapy are developing continuously and are gaining recognition; eventually, they face the inevitable challenge of drug resistance. Nanotechnology has several important effects on lung cancer treatment, owing to its unique propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“…The tumor-associated antigens released from the broken tumor tissue are processed and presented by the antigen-presenting cells (APCs), which are then delivered to T cells to produce an immune response. Of course, original tumor tissue can also transmit signals to APC for immune response (Li et al 2021 ) (Fig. 1 ).…”
Section: Application Of Nanoparticles In the Treatment Of Lung Cancermentioning
confidence: 99%
“…The tumor-associated antigens released from the broken tumor tissue are processed and presented by the antigen-presenting cells (APCs), which are then delivered to T cells to produce an immune response. Of course, original tumor tissue can also transmit signals to APC for immune response (Li et al 2021 ) (Fig. 1 ).…”
Section: Application Of Nanoparticles In the Treatment Of Lung Cancermentioning
confidence: 99%
“…Nanomedicine is emerging as a new method that does not produce drug resistance, can prevent tumor metastasis and recurrence, and has low toxicity ( Markman et al, 2013 ; Hussain 2016 ; Li et al, 2021 ). It was recently shown that nanomedicine endocytosis has better treatment effect and weak side effects after accumulation in tumor tissues through passive enhanced permeability and retention (EPR) action of tumors ( Nehoff et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The employment of nano-based drug delivery system (DDS) opened a new avenue to integrate multiple anticancer agents in one platform for more efficacious therapeutic outcome with reduced side effects and enhanced targeting ability [ 11 – 13 ]. Due to their unique potential for passive targeting through enhanced permeability and retention (EPR), high surface area for drug loading and modification, and prolonged plasma half-life, nanomedicine possesses numerous benefits over the conventional therapeutic modalities [ 14 16 ]. In this field, many nanocarriers like liposomes, micelles, reconstituted high-density lipoprotein (rHDL), metallic NPs, hybrid NPs, nanogel, nanoemulsion, black phosphorus, carbon-related nanomaterials, and other inorganic nanomaterials have been extensively explored in anticancer drug delivery both clinically and pre-clinically [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%